PENGARUH KOMPETENSI KEPRIBADIAN GURU PAI TERHADAP PRESTASI BELAJAR SISWA - Maskhuroh, Lailatul; Zuliani, Siti; Widari, Widari (ILJ: Islamic Learning Journal, 2024)
The aim of this research is to determine: PAI teacher personality competence, student learning achievement and whether there is an influence of PAI teacher personality competence on student learning achievement at Pancasila Mojowarno Middle School, Jombang. This research uses quantitative research with a survey research design. The data collection technique uses a questionnaire, while the data analysis technique uses Spearman rank correlation. . The research results are: a. The personality competency of PAI teachers at Pancasila Middle School Mojowarno Jombang is in the medium category, because it has an average score of 150 and Std. Daviation (SD) is 21 where a value of 150 is located in the interval 146 < X ? 167 in the medium category. b. Student learning achievement at SMP Pancasila Mojowarno Jombang is included in the medium category, because it has an average score (Mean) of 79 and Std. Daviation (SD) is 4 where the value 79 is located in the interval 77 < X ? 81 in the medium category. c. There is a relationship between variable X (personal competence of PAI teachers) and variable Y (student learning achievement) with the Sig value. (2-Tailed) is 0.000 < 0.05, while the level of strength (Closeness) is in the weak category, this is proven by the correlation coefficient value of 0.359. The direction (type) of the relationship between the two variables is positive, which means that if the PAI teacher's personality competence is increased, student learning achievement will increase.